Pengaruh Lingkungan Kerja, Pengawasan, Dan Kompensasi Terhadap Kinerja Pegawai Dengan Disiplin Kerja Sebagai Variabel Intervening Pada Pengadilan Agama Di Lingkungan Provinsi Gorontalo - Moh. Rolli Paramata; Moh. Afan Suyanto; Silviana Taniu; Nur Isna Ningsih Katili (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
The aim of this study is to analyze the effects of the work environment, supervision, and compensation on employee performance, with work discipline as an intervening variable, at the Religious Courts in Gorontalo Province. This research employed a census sampling method, involving 120 respondents, and used path analysis for data evaluation. The results of the path analysis show that the work environment can enhance performance through work discipline, whereas supervision does not have a significant indirect effect on performance through work discipline, indicating that work discipline does not mediate the relationship between supervision and employee performance. Conversely, compensation has a positive and significant effect on performance through work discipline, indicating that fair compensation, supported by high work discipline, can further improve employee performance. These findings emphasize the importance of creating a conducive work environment, providing fair compensation, and implementing effective supervision to enhance discipline and performance among employees in the Religious Courts of Gorontalo Province.